(untitled) (Research, Society and Development, 2021)
Plant growth regulators in the germination of Diospyros hispida A. DC. (Ebenaceae) Seed. Diospyros hispida species is a native fruit that has long germination period, hindering seedling production. The aim of this work was to evaluate the germination of Diospyros hispida seeds under the effect of gibberellic acid and biostimulant applications. Four replicates of 25 seeds per treatment were used. Treatments were: T1 - distilled water, T2, T3 and T4 - GA3 solutions at 100, 150 and 200 mg L-1, respectively, T5 - Immersion for 24 hours in distilled water with aeration, T6, T7 and T8 - Immersion for 24 hours in aerated GA3 solutions at 100, 150 and 200 mg L-1, respectively, T9, T10 and T11 - biostimulant application (containing auxin, gibberellin and cytokinin) at 3, 5 and 7 ml kg-1 of seeds. Germination rate, mean germination time, germination speed index, synchronization index, relative germination frequency, normal seedlings, root length, shoot length and seedling dry mass were evaluated. The effect of gibberellic acid and biostimulant containing auxin, gibberellin and cytokinin negatively influenced Diospyros hispida germination under the conditions of this study.